Implementing Non-Formal Learning in a Formal Environment (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
This presentation examined how digital badges can support the recognition of competencies developed in non-formal contexts by fostering collaboration among stakeholders and by building shared frameworks for describing and validating competencies. It starts from a simple but important premise: before designing recognition systems, stakeholders must first agree on what is meant by “competence.” From this perspective, an individual can be considered competent when they are able to act effectively according to expected criteria (“power to act”) and when they can adapt their action across diverse contexts by mobilizing appropriate resources and learning from experience (“knowing how to act”).  Based on this understanding, competency recognition can pursue two complementary objectives. The first is evaluative, making competencies visible and assessable through explicit criteria. The second is transformative, supporting the development of practice by encouraging reflection, adaptation, and continuous learning. Recognition thus becomes not only a mechanism for assessment but also a lever for professional and collective development.  A central argument of the presentation is that recognition systems become meaningful only when they are co-constructed with the stakeholders concerned. Designing digital badges collaboratively with educators, professionals, organizations, and learners helps ensure that the resulting system reflects real practices and shared expectations. This collaborative approach contributes to the creation of a common language around competencies and engagement, enabling clearer dialogue between actors and increasing the visibility of individual contributions within organizations and territories. Digital badges function as mediating objects that make competencies and commitments more visible and easier to discuss.  Finally, the presentation highlighted the importance of developing shared competency frameworks that support professional practices while remaining flexible and evolving. Such frameworks can help harmonize practices and reassure professionals by providing a shared reference. However, they should not become rigid, top-down standards. Instead, they should remain dynamic tools, continuously enriched and adjusted through the concrete experience of the communities that use them. In this way, competency frameworks and digital badges together contribute to building a living ecosystem of recognition grounded in practice. Keywords: non-formal learning, competence frameworks, collaborative recognition